Avian biodiversity and abundance at the CSU Mountain Campus: an acoustic monitoring study - Doorack, Emily, author (Colorado State University. Libraries, 2024)
The research conducted for this thesis and the overarching project encompassing it measured the biodiversity of avian species present at the CSU Mountain Campus through auditory data collection. We deployed auditory recording devices at the beginning of the summer of 2024 and allowed them to record data on the calls of avian species present across the campus until the end of the summer. We found that the standing forest habitat of mixed conifers had the highest amount of call activity, but the lowest amount of unique calls associated with it. However, the devices deployed in the riparian and the burn stand habitat zones had much higher diversity and unique species despite having a lower volume of recorded calls. Because unique species were found throughout the campus and there was a high number and diversity of calls at each of the three habitat types, we encourage future management and conservation of the CSU Mountain Campus to incorporate all three of these habitat types into land management practices. This is of extreme importance as the campus continues to grow and usage of the trails through these habitat types increases, potentially affecting the avian populations present.
Colorado State University; University Honors Program; Warner College of Natural Resources; Department of Fish, Wildlife and Conservation Biology.
Keywords: avian; biodiversity; Mountain Campus; mixed conifer forest; riparian; burn scar; acoustic; bird